Implementation of Tazqiyah An- Nafs as an effort to build a relationship with God - Muhammad Shendyka; Cucu Surahman; Ariq Muammar; Pitra Gosha Patriasya (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2025)
Study This aim Forstudy meaning practice paragraph qad aflaha man zakkāhā (QS. Asy-Syams) in perspectives of interpretation and Sufism, as well formulate framework implementative purification soul (tazkiyat al-nafs) which is relevant with human spiritual challenges contemporary. Depart from the reduction problem tazkiyah as draft normative-abstract, study This put paragraph the as foundation ethical - spiritual demands transformation self in a way conscious, directed, and sustainable. Research This use method qualitative based studies library research with approach analysis thematic to primary sources of Sufism classic, especially works of Al- Ghazālī , Ibn 'Arabī, and Shaykh 'Abd al-Qādir al-Jīlānī, as well as critical dialogue with interpretations of the Koran and literature academic contemporary. Research results show that purification soul in tradition Sufism No can realized in a way partial, but rather necessitate integration three main processes: tazkiyat al- nafs (submission) encouragement egocentric), tashfiyat al-qalb (purification) heart), and taḥliyat al- ruḥ (clarification soul). Riyā ḍah al- nafs positioned as instrument supportive practices​ tazkiyah, while relation guidance between students and mursyid functioning as mechanism pedagogical Forguard monotheistic orientation and preventing illusion piety. In addition, research This confirm that twenty​ spiritual nature formulated by Ibn ' Arabī is a systematic and applicable ethical -spiritual model in form human Kamil, and play a role as buffer balance between discipline external and internal inner. Research conclusion This confirm that Surah Asy-Syams give contribution significant conceptual​ in bridge gap between normativity text of the Qur'an and needs spiritual practices of modern humans. Findings This enrich treasury studies Sufism with offer framework integrative tazkiyah that can appliedin spiritual education, coaching religious, and development ethics religious contemporary , at the same time open room for study continuation of the study implementation of the tazkiyah model This in context more social and educational​ wide